Precise Underwater Distance Measurement by Dual Acoustic Frequency Combs. Issue 9 (5th August 2019) - Wu, Hanzhong; Qian, Zhiwen; Zhang, Haoyun; Xu, Xinyang; Xue, Bin; Zhai, Jingsheng
Abstract: Underwater acoustics is of fundamental importance for marine science and technology. However, acoustic waves transmitted by state‐of‐the‐art underwater acoustic systems are not inherently phase locked, which hinders the development of underwater acoustic technology. For example, the precision of underwater distance measurement can only achieve centimeter level. As a versatile tool, optical frequency combs have enabled revolutionary progress in optical metrology and precision measurement. In parallel with optical frequency combs, here, the generation of fully stabilized, underwater acoustic frequency combs is reported, in which equidistant acoustic modes are produced via a hydroacoustic transducer. The precision of each individual acoustic mode is measured to be 10 −9 at 1 s and 10 −12 at 1000 s averaging times. Underwater distance measurements are carried out in an anechoic pool using a dual‐comb scheme. Comparison with reference values shows consistency within 50 µm (7 × 10 −6 in relative). The relatively long‐duration experiments at 7 m distance yield an Allan deviation of 1.8 µm (2.6 × 10 −7 in relative) at 1 s and further 480 nm (6.8 × 10 −8 in relative) at 40 s averaging times. The approach to acoustic frequency comb generation offers a promising and powerful platform for future underwater distance measurement, positioning, and navigation. Abstract : Underwater acoustics is of fundamental importance for marine science and technology. Here, the generation of fully‐stabilized acoustic frequency combs has been reported for the first time. Underwater long distance measurement has been carried out, and the measurement uncertainty can achieve 50 µm. This offers a promising and powerful platform for future underwater distance measurement, positioning, and navigation.